Using accreditation reports to measure performance: from expectations to reality. (1st March 2011) - Lavoie, A; Moore, L; Murat, V; Bamvita, J M; Lapointe, J; Bourgeois, G
Abstract : The American College of Surgeons has published criteria for trauma centre accreditation since the 1970s. Following their initial designation as trauma centres in 1993-95, 59 hospitals in the province of Quebec, Canada, were evaluated in situ by an external panel of experts in two waves: 1995–2000 and 2000–2005. Objective: Evaluate whether accreditation assessment reports can be used to measure the structural performance of trauma centres. Methods: Both a qualitative and a quantitative analysis of the accreditation reports were performed. A standardised evaluation grid involving three major themes (commitment, program and procedures) and measuring 84 elements was applied. In total, 115 evaluations (three were missing), were retrospectively analysed. Results: The reports reflect the hospitals' performance but also convey political strategies, primarily aiming to stimulate the best performers and to avoid discouraging poor performers. After initial designation, the first wave produced higher performance scores than the second wave, with means of 46.3 (+-7.25) and 48.6 (+-12.9) respectively. This reflects the harsher judgment on repeating offenders during the second wave. No correlation was observed between scores from the two waves (Spearman's rho 0.03, p=0.822). Conclusion: Trauma centre evaluation through expert panel site visits is an international norm. It is however expensive and time consuming. In this system, such evaluations do assess a trauma centre's structure performance but also convey political preoccupations. Improvement lies in a more systematic reporting of site visits by the experts.